SERS-Based Immunoassays for the Detection of Botulinum Toxins A and B Using Magnetic Beads - Kihyun Kim (Sensors, 2019)
Rapid and sensitive detection of botulinum neurotoxins (BoNTs) is important for immediate treatment with proper antitoxins. However, it is difficult to detect BoNTs at the acute phase of infection, owing to its rarity and ambiguous symptoms. To resolve this problem, we developed a surface-enhanced Raman scattering (SERS)-based immunoassay technique for the rapid and sensitive detection of BoNTs. Magnetic beads and SERS nanotags as capture substrates and detection probes, respectively, and Nile Blue A (NBA) and malachite green isothiocyanate (MGITC) as Raman reporter molecules were used for the detection of two different types of BoNTs (types A and B), respectively. The corresponding limits of detection (LODs) were determined as 5.7 ng/mL (type A) and 1.3 ng/mL (type B). Total assay time, including that for immunoreaction, washing, and detection, was less than 2 h.